2018
DOI: 10.1186/s40168-017-0395-y
|View full text |Cite
|
Sign up to set email alerts
|

Haemophilus is overrepresented in the nasopharynx of infants hospitalized with RSV infection and associated with increased viral load and enhanced mucosal CXCL8 responses

Abstract: BackgroundWhile almost all infants are infected with respiratory syncytial virus (RSV) before the age of 2 years, only a small percentage develops severe disease. Previous studies suggest that the nasopharyngeal microbiome affects disease development. We therefore studied the effect of the nasopharyngeal microbiome on viral load and mucosal cytokine responses, two important factors influencing the pathophysiology of RSV disease. To determine the relation between (i) the microbiome of the upper respiratory trac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
72
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(80 citation statements)
references
References 52 publications
(66 reference statements)
7
72
0
1
Order By: Relevance
“…Here, the authors show a shift from a Staphylococcus dominated microbiome in uninfected infants to a Moraxella, Streptococcus, Corynebacterium, Haemophilus, and Dolosigranulum dominated respiratory microbiome in RV and RSV infected patients. The predominance of Haemophilus in RSV infected lung has been corroborated by an independent study by Ederveen et al (109). There are interesting points to be taken from these studies.…”
Section: Viral Infections Of the Lungmentioning
confidence: 60%
“…Here, the authors show a shift from a Staphylococcus dominated microbiome in uninfected infants to a Moraxella, Streptococcus, Corynebacterium, Haemophilus, and Dolosigranulum dominated respiratory microbiome in RV and RSV infected patients. The predominance of Haemophilus in RSV infected lung has been corroborated by an independent study by Ederveen et al (109). There are interesting points to be taken from these studies.…”
Section: Viral Infections Of the Lungmentioning
confidence: 60%
“…24,26,27 In this study, we observed that in infants who later developed recurrent wheezing, there was a higher abundance of Proteobacteria. 30 Although the exact mechanism(s) by which the airway microbiota influences the pattern of airway inflammatory response during RSV bronchiolitis is unclear, it may be partly due to the higher level of LPS produced by these Gram-negative pathogenic bacteria observed in this study. Airway chronic bacterial colonization and endotoxin exposure might induce persistent activation of the innate immune system resulting in the production of pro-inflammatory cytokines in airway.…”
Section: Discussionmentioning
confidence: 82%
“…During viral respiratory infections, alpha-diversity and richness were suggested to be lower [55] and to potentially drive symptom severity [47], in particular when RSV is the aetiological agent [58]. However, these findings are not consistently found [16,59,60].…”
Section: Respiratory Microbiota Impacts Bronchiolitis In Childrenmentioning
confidence: 98%